Daily Adolescent Sugar-Sweetened Beverage Intake Is Associated With Select Adolescent, Not Parent, Attitudes About Limiting Sugary Drink and Junk Food Intake. Issue 1 (January 2020) - Imoisili, Omoye E.; Park, Sohyun; Lundeen, Elizabeth A.; Yaroch, Amy L.; Blanck, Heidi M.
Purpose: To examine associations of adolescent sugar-sweetened beverage (SSB) intake with parent SSB intake and parent and adolescent attitudes about limiting SSB and junk food (SSB/JF) intake. Design: Quantitative, cross-sectional study. Setting: The 2014 Family Life, Activity, Sun, Health, and Eating study. Sample: Parent–adolescent dyads (N = 1555). Measures: The outcome was adolescent SSB intake. Exposure variables were parent SSB intake, sociodemographics, and parent and adolescent attitudes about SSB/JF intake (responses: agree, neither, or disagree). Analysis: Multinomial logistic regressions estimated adjusted odds ratios (aOR) and 95% confidence intervals (CIs). Results: Half (49.5%) of adolescents and 33.7% of parents consumed SSB ≥1 time/day. Parent daily SSB intake was associated with adolescent daily SSB intake (aOR = 8.9; CI = 4.6-17.3) [referent: no consumption]. Adolescents who disagreed on having confidence to limit SSB/JF intake had higher odds of daily SSB intake (aOR = 3.5; CI = 1.8-6.8), as did those who disagreed they felt bad about themselves if they did not limit SSB/JF intake (aOR = 1.9; CI=1.1-3.3), compared to adolescents who agreed with these attitudes. No parental attitudes were significant. Conclusion: Higher odds of daily SSB intake among adolescents was associated with parent SSB intake and adolescent attitudes about confidence in, and feeling bad about, limiting SSB/JF intake. Parent attitudes were not associated with daily adolescent SSB intake. Efforts to reduce adolescent SSB intake could consider strategies geared toward improving adolescent attitudes and dietary behaviors and parental SSB intake.